The Role of Amanah and Reputation in Improving the Performance: Literature Review (Architecture Image Studies, 2025)
This study examines the role of amanah (trustworthiness) and reputation in enhancing the organizational performance of Islamic private universities in Central Java. Drawing on resource-based theory (RBT) and the concept of Organizational Citizenship Behavior (OCB), the research investigates how amanah reputation ethic, amanah reputation work environment, and amanah reputation social responsibility influence OCB and, subsequently, organizational performance. This paper uses a literature review from textbooks and articles with conceptual and empirical findings sourced from Scopus, WoS, ScienceDirect, Emerald, MDPI, and Google Scholar, examining organizational performance at individual, team, and organizational levels. Findings reveal that ethical reputation actively drives organizational success by embedding ethics into corporate identity, fostering trust, and sustaining growth. A supportive work environment enhances reputation, performance, and resilience in evolving markets. Social responsibility is a strategic necessity, strengthening reputation and long-term success. Organizational Citizenship Behavior fosters innovation, excellence, and stakeholder value, driving sustainable growth.